2022
DOI: 10.21134/pssa.v10i1.801
|View full text |Cite
|
Sign up to set email alerts
|

Afectividad, Regulación Emocional, Estrés y Salud Mental en adolescentes del Ecuador en tiempos de pandemia

Abstract: Marco Teórico. La adolescencia supone una etapa crucial en el desarrollo humano, producto de cambios biopsicosociales, que impactaran a futuro la salud mental. El objetivo es identificar la relación que guardan la afectividad, las dificultades de regulación emocional y el estrés en la salud mental en una muestra de adolescentes de bachillerato del Ecuador. Método. Estudio de tipo descriptivo, correlacional, comparativo por género y de corte transversal, con las pruebas de Afectos Positivos y Negativos, de Difi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
5
0
5
Order By: Relevance
“…In addition, other psychological symptoms are presented, in which somatic symptoms and anxiety/insomnia prevail. These findings are consistent with similar preliminary reports from the current pandemic (García-Espinosa et al, 2021;Gloster et al, 2020;Salari et al, 2020;) including Ecuador (Tusev et al, 2020;Zumba-Tello & Moreta-Herrera, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, other psychological symptoms are presented, in which somatic symptoms and anxiety/insomnia prevail. These findings are consistent with similar preliminary reports from the current pandemic (García-Espinosa et al, 2021;Gloster et al, 2020;Salari et al, 2020;) including Ecuador (Tusev et al, 2020;Zumba-Tello & Moreta-Herrera, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…(García-Espinosa et al, 2021). In Ecuador, there is evidence of the prevalence of anxiety (19.4%), depression (10.3%), and stress (13.5%) in the adult population (Tusev et al, 2020;Zumba-Tello & Moreta-Herrera, 2022). Hence, it is important to explore this phenomenon to have a better approximation of future effects.…”
Section: Covid-19 and Mental Healthmentioning
confidence: 99%
“…Within this contextual framework, studies in the adolescent population found that mental health is associated with suicidal ideation [ 21 ], difficulties in emotional regulation and its relationship with aggression [ 22 ], stress [ 23 ], affectivity, and quality of life [ 24 ]. In addition, studies reported that the absence of family communication [ 25 ], domestic violence [ 26 ], and inappropriate parenting practices [ 27 ] negatively influence mental health.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed, for example, that adolescents present higher impulsivity when compared to adults [5]. Studies report the presence of mental disorders in adolescence to be between 18% and 30% [6], with social dysfunction and anxiety the most prevalent, followed by somatisation and depression [7]. However, identifying these symptoms can be difficult in Latin-American countries due to the limited availability of instruments adapted locally.…”
Section: Introductionmentioning
confidence: 99%